2016
DOI: 10.1016/j.molmed.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of In Utero Exposure to Malaria on Fetal T Cell Immunity

Abstract: Pregnancy-associated malaria, including placental malaria, causes significant morbidity and mortality worldwide. Recently, it has been suggested that in utero exposure of the fetus to malaria antigens may negatively impact the developing immune system and result in tolerance to malaria. Here, we review our current knowledge of fetal immunity to malaria, focusing on the dynamic interactions between maternal malaria infection, placental development and the fetal immune system. A better understanding of the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 111 publications
2
20
0
Order By: Relevance
“…The findings of this study of hyperparasitaemia in infants prenatally exposed to P. falciparum may suggest inappropriate anti parasitic protective immunity. This suggestion is supported by observations from previous studies indicating that prenatal exposure to P. falciparum affected development of fetal regulatory and effector T cell responses [ 14 , 15 ]. The effect of prenatal exposure to P. falciparum on fetal immune cells may persist to childhood; leading to inappropriate anti-parasitic immunity and failure of effective immune response to control parasite replication during clinical malaria episodes, with subsequent hyperparasitaemia.…”
Section: Main Textsupporting
confidence: 85%
“…The findings of this study of hyperparasitaemia in infants prenatally exposed to P. falciparum may suggest inappropriate anti parasitic protective immunity. This suggestion is supported by observations from previous studies indicating that prenatal exposure to P. falciparum affected development of fetal regulatory and effector T cell responses [ 14 , 15 ]. The effect of prenatal exposure to P. falciparum on fetal immune cells may persist to childhood; leading to inappropriate anti-parasitic immunity and failure of effective immune response to control parasite replication during clinical malaria episodes, with subsequent hyperparasitaemia.…”
Section: Main Textsupporting
confidence: 85%
“…Further investigations regarding their safety and efficacy, also considering population dependent variances in protectivity, need to be conducted. Additionally, an interesting new area of research is the recently reviewed fetal in utero immune response against malaria, its effect during childhood, and differences based on sex [22,30].…”
Section: Further Investigationmentioning
confidence: 99%
“…It has been shown that histopathological changes and placental malaria enhance the risk of preeclampsia in pregnant women, especially in primigravidas [29]. Histopathological changes during placental malaria include presence of hemozoin, perivillous fibrin deposition [30,31], syncytial knot formation [32], and decrease in villous surface area (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women are at an increased of placental P. falciparum infections, the scope of which can be found reviewed elsewhere . Relevant to this review is the consideration of localized immune modifications during antenatal infections that could impact an infant's ability to mount a protective immune response to malaria . Pregnancy‐associated malaria studies highlight the concept that humans may not be immunologically naĂŻve, even at birth, which could be an effect modifier when interpreting the function of immune mediators during early childhood.…”
Section: Overview Of Malariamentioning
confidence: 99%